2018
DOI: 10.1016/j.rehab.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Cueing for people with Parkinson's disease with freezing of gait: A narrative review of the state-of-the-art and novel perspectives

Abstract: Freezing, which manifests during gait and other movements, is an incapacitating motor symptom experienced by many patients with Parkinson's disease (PD). In rehabilitation, auditory and visual cueing methods are commonly applied to evoke a more goal-directed type of motor control and, as such, reduce freezing severity in patients with PD. In this narrative review, we summarize the current evidence regarding the effects of external cueing in patients with PD with freezing of gait (FOG) and provide suggestions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
184
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 224 publications
(196 citation statements)
references
References 57 publications
6
184
1
5
Order By: Relevance
“…Our results may also have translational implications. Presentation of salient cues to patients with Parkinson's disease can improve symptoms, for example by overcoming freezing of gait (Gilat et al, 2018;Ginis et al, 2017). If elevated DA levels constitute an underlying mechanism, then our data indicate that adding cues may recruit otherwise silent VTA DA neurons, which are less affected by neurodegeneration than SNc neurons (Surmeier et al, 2017) and could partially compensate in regions where SNc and VTA projections overlap.…”
Section: Kremer Et Al Multiplexed Damentioning
confidence: 75%
“…Our results may also have translational implications. Presentation of salient cues to patients with Parkinson's disease can improve symptoms, for example by overcoming freezing of gait (Gilat et al, 2018;Ginis et al, 2017). If elevated DA levels constitute an underlying mechanism, then our data indicate that adding cues may recruit otherwise silent VTA DA neurons, which are less affected by neurodegeneration than SNc neurons (Surmeier et al, 2017) and could partially compensate in regions where SNc and VTA projections overlap.…”
Section: Kremer Et Al Multiplexed Damentioning
confidence: 75%
“…With wearable technology, it could be possible to sense a sudden deterioration in gait pattern that would anticipate a FOG episode and then deliver an immediate cue at that time, to prevent the occurrence of FOG. This has been referred to as intelligent cueing, as recently described in a comprehensive review …”
Section: Assessing the Presence And Severity Of Fog With Wearable Senmentioning
confidence: 99%
“…Cueing can be defined as a mechanism of applying a spatial or a temporal stimulus to facilitate initiating or maintaining motor activity [32]. Numerous studies have shown that external cueing can improve the amplitude and timing of the intended movement by increasing body position/movement awareness, making it a suitable modality for gait and posture rehabilitation [25,26,[36][37][38][39][40]. In addition, cueing has also been increasingly used in helping with the initiation of a movement [41].…”
Section: Cueing For Rehabilitation In Pdmentioning
confidence: 99%
“…For people in the early stage of disease severity, external cues can compensate for small deviations from their normal gait pattern thereby maintaining optimal gait quality and preventing deconditioning through training. Severely affected individuals with PD rely on external cues to compensate for deficits in the automatic control mechanisms (i.e., the ability to automatically generate normal stride length in a timely manner) thus improving gait and reducing the incidence of falls and freezing of gait [30,32,37,55].…”
Section: Effect Of Disease Stage On Cueing Strategymentioning
confidence: 99%